Correlation of vitamin A levels in umbilical cord blood with neonatal pulmonary diseases - Yu Wei; Hong-Liang Zhang; Ya-Zhou Sun; Jin-Peng Yang; Shu-Jun Li (Pediatrics and Neonatology)
Objective: To study the relationship between umbilical cord blood vitamin A (VA) and neonatal lung diseases and explore the impact of umbilical cord blood VA on neonatal lung diseases. Method: Umbilical vein blood was collected at birth, and its VA content was measured. According to the VA levels in umbilical cord blood, a VA deficiency (VAD) group, a marginal deficiency group and a normal group were created and followed up until 28 days after birth. Results: The umbilical cord blood VA level in the neonatal group with lung disease was 0.13 ± 0.05 mg/L, while the result for the VA level in the non-lung disease group was 0.15 ± 0.05 mg/L. The umbilical cord blood VA levels in the neonatal lung disease group were significantly lower than those in the non-lung disease group. The incidence of neonatal pulmonary diseases was highest in the VAD group, and the incidence decreased as the level of VA in umbilical cord blood increased. Umbilical cord blood VAD and premature birth were found to be independent risk factors for neonatal respiratory disease. Conclusion: Umbilical cord blood VAD and premature birth are independent risk factors for neonatal pulmonary diseases. The lower the level of VA in umbilical cord blood, the more susceptible infants will be to neonatal respiratory infections in the neonatal period.